The crystal structure of DR6 in complex with the amyloid precursor protein provides insight into death receptor activation - Xu, Kai (Genes Dev, 2015)
The amyloid precursor protein (APP) has garnered considerable attention due to its genetic links to Alzheimer's disease. Death receptor 6 (DR6) was recently shown to bind APP via the protein extracellular regions, stimulate axonal pruning, and inhibit synapse formation. Here, we report the crystal structure of the DR6 ectodomain in complex with the E2 domain of APP and show that it supports a model for APP-induced dimerization and activation of cell surface DR6.